Simulação e análise do mercado gerado por spammers e potenciais consumidores - Cesar Fernandes Teixeira (2009)
Spam is an important problem that incurs in huge financial losses.However, spam is based on consumption. The existence, or thepossibility of existence, of a demand generates a supply offeredthrough spam.Therefore, understanding this market generated by spammers andpotential consumers is imperative. This is due to the fact thatunderstanding this market can bring valuable information about theeffects of fundamental factors, the consequences and deficiencies ofthe available anti-spam techniques, and to propose alternatives.This work creates a model, based on agents and in economics conceptsand models, of the market behind spam. Moreover, the analysis donecontributes to understanding spam and its market, to inferring theconsequences, in this market, of the usual anti-spam techniques. As afinal goal, suggestions about improvements and new strategies areproposed.